2021
DOI: 10.1186/s12967-021-02842-1
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the PI3K and MAPK pathways to improve response to HER2-targeted therapies in HER2-positive gastric cancer

Abstract: Background Aberrant PI3K signalling is implicated in trastuzumab resistance in HER2-positive gastric cancer (GC). The role of PI3K or MEK inhibitors in sensitising HER2-positive GCs to trastuzumab or in overcoming trastuzumab resistance is unclear. Methods Using mass spectrometry-based genotyping we analysed 105 hotspot, non-synonymous somatic mutations in PIK3CA and ERBB-family (EGFR, ERBB2, ERBB3 and ERBB4) genes in gastric tumour samples from 69… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 55 publications
(33 reference statements)
0
16
0
Order By: Relevance
“…Further research is needed to determine if other inhibitor combinations are safe and can improve patient outcomes. Finally, PTEN mutations promote MAPK pathway dependency in breast cancer [ 78 ]; the combination of PI3K and MEK inhibitors have been shown to improve responses to HER2+ gastric cancer [ 79 ], and future research is needed to determine if this combination could improve outcomes in patients with HER2+ breast cancer.…”
Section: Mechanisms Of Resistancementioning
confidence: 99%
“…Further research is needed to determine if other inhibitor combinations are safe and can improve patient outcomes. Finally, PTEN mutations promote MAPK pathway dependency in breast cancer [ 78 ]; the combination of PI3K and MEK inhibitors have been shown to improve responses to HER2+ gastric cancer [ 79 ], and future research is needed to determine if this combination could improve outcomes in patients with HER2+ breast cancer.…”
Section: Mechanisms Of Resistancementioning
confidence: 99%
“…A positive effect on metastatic spread can be achieved with sorafenib monotherapy and combination therapy. When used in combination, refametinib and sorafenib act synergistically in multiple models to reduce tumour growth and prolong survival 28–31 . In addition, trametinib has been reported to inhibit the growth of ERRα and KRAS‐mutant lung cancer in different cancers 32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…When used in combination, refametinib and sorafenib act synergistically in multiple models to reduce tumour growth and prolong survival. [28][29][30][31] In addition, trametinib has been reported to inhibit the growth of ERRα and KRAS-mutant lung cancer in different cancers. 32,33 Although reduced TNFα production was observed in vivo, the combination therapy activated CD8+ T cell-mediated immunity and increased survival in an immunoreactive mouse model carrying glioma.…”
Section: Pharmacogenetic Screening For Potential Drugs That Inhibit Lsm1mentioning
confidence: 99%
“…63 In addition, some studies have shown that inhibition of PI3K or MEK alone, or in combination with anti-HER-2 therapy, might be a reformative treatment scheme for some patients with HER-2 positive GC. 64 Approximately 34-59% of the patients with HER-2 positive GC also overexpress HER-3 and are resistant to trastuzumab, 65 which can be attributed to the negative feedback regulation of HER-3 mediated by the HER-2-dependent P13K-AKT pathway, making trastuzumab unresponsive to ligand-dependent dimerization of HER-2/HER-3. 66…”
Section: Her-2/her-3 Dimer In Gcmentioning
confidence: 99%